2009
DOI: 10.1111/j.1755-3768.2009.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of ocular blood flow with haemorheological parameters in primary open-angle and exfoliative glaucoma

Abstract: ABSTRACT.Purpose: To evaluate the ocular blood flow velocities and haemorheological parameters in patients with primary open-angle glaucoma (POAG), exfoliative glaucoma (XFG) and exfoliation syndrome (XFS) and to compare their results with those of healthy controls. Methods: Twenty-five patients with POAG (group 1), 25 patients with XFG (group 2), 25 patients with XFS (group 3) and 25 healthy controls (group 4) were included in the study. Ocular blood flow velocities of ophthalmic artery (OA), central retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…This means that RBC deformability was measured at high shear stresses, which actually do not match with the wall shear stress values of retinal vessels in these studies. On the other hand, Sekeroglu et al measured RBC deformability of POAG patients at shear stresses of 3 and 30 Pa and found no difference. In the present study, RBC deformability was measured using LORCA but in a wider range of shear stresses between 0.30 and 30 Pa covering the average wall shear stress values of retinal vessels.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This means that RBC deformability was measured at high shear stresses, which actually do not match with the wall shear stress values of retinal vessels in these studies. On the other hand, Sekeroglu et al measured RBC deformability of POAG patients at shear stresses of 3 and 30 Pa and found no difference. In the present study, RBC deformability was measured using LORCA but in a wider range of shear stresses between 0.30 and 30 Pa covering the average wall shear stress values of retinal vessels.…”
Section: Discussionmentioning
confidence: 98%
“…19 Only a few studies evaluated erythrocyte aggregation and deformability in glaucoma patients and these studies used different laboratory techniques and patient selection criteria. 2,5,[15][16][17][19][20][21] Cheng et al 15 and Vetrugno et al 19 using ektacytometry, demonstrated a lower index of erythrocyte deformability in patients with normal tension glaucoma (NTG). Ates et al 5 found no difference in RBC deformability in normal tension glaucoma and high tension glaucoma using the Cell Transit Analyser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of factors such as age, gender, menopausal status and systemic disease or drugs on the ocular blood flow has been widely investigated in many reports (Kavroulaki et al. 2010; Sekeroglu et al. 2011; Shoshani et al.…”
Section: Methodsmentioning
confidence: 99%
“…Оценка степени взаимосвязи показателей офтальмогемодинамики и реологических свойств крови при глаукоме является непростой задачей и нуждается в дальнейшей детализации и уточнении. Это обусловлено тем, что при ПОУГ часто выявляют изменения показателей гемодинамики (снижение скоростных показателей и повышение индексов периферического сопротивления по данным ЦДК), которые могут не зависеть от вязкости крови, но совпадать с подобными изменениями по форме проявления [9].…”
unclassified